Energy Dissipation from Vibrating Floor Slabs due to Human-Structure Interaction - James M.W. Brownjohn (Shock and Vibration)
Lightweight pre-cast flooring systems using post-tensioning to increase strength but not stiffness are increasingly popular, and vibration serviceability problems tend to govern design of such floors where human occupants are increasingly concerned with vibrations. At the same time as inducing response, stationary human observers can also participate in the response as mitigating influence and it is clear that a human behaves as a highly effective damper, even when seated.